2003
DOI: 10.1111/1469-7610.00159
|View full text |Cite
|
Sign up to set email alerts
|

Social anxiety in childhood: the relationship with self and observer rated social skills

Abstract: Socially anxious children may not necessarily lack social skills. Rather, their deficits may relate to nervousness and appraisals of their skills. Treatment programmes for these children should take care to assess social skills carefully before prescribing social skill remediation, and should consider employing a cognitive element to tackle negative misperceptions of subjective social skill.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
117
3
8

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 103 publications
(144 citation statements)
references
References 17 publications
16
117
3
8
Order By: Relevance
“…[60,61] These same visible anxiety factor and social behavior factors were found in SAD children while performing social tasks. [62] Therefore, showing visible anxiety symptoms appears to be a different dimension from social behavior in SAD.…”
Section: Fear Of Showing Anxiety Symptomsmentioning
confidence: 99%
“…[60,61] These same visible anxiety factor and social behavior factors were found in SAD children while performing social tasks. [62] Therefore, showing visible anxiety symptoms appears to be a different dimension from social behavior in SAD.…”
Section: Fear Of Showing Anxiety Symptomsmentioning
confidence: 99%
“…Several studies have reported that social anxiety in children is associated with less competent social skills based on observer ratings, suggesting that children who are socially anxious may have a genuine social skill deficit (Alfano, et al, 2006;Beidel, Turner, & Morris, 1999;Inderbitzen-Nolan, et al, 2007;Spence, et al, 1999). However, this is not consistently found across studies (Cartwright-Hatton, et al, 2003;Cartwright-Hatton, et al, 2005;Erath, Flanagan, & Bierman, 2007). In general, social skill deficits tend to be found more consistently in clinically anxious participants rather than in samples of typically-developing participants with high scores on questionnaire measures of social anxiety (Levitan & Nardi, 2009).…”
Section: State Anxiety and Social Skillmentioning
confidence: 99%
“…In examining the causes of these social difficulties, research has provided some evidence that socially anxious children may exhibit impairments in social skill (Alfano, Beidel, & Turner, 2006;Inderbitzen-Nolan, Anderson, & Johnson, 2007;Spence, Donovan, & Brechman-Toussaint, 1999). However, there is some inconsistency in these findings and recent research has suggested that anxious children may perceive themselves as having poor social skills when in fact they do not (Cartwright-Hatton, Hodges, & Porter, 2003;Cartwright-Hatton, Tschernitz, & Gomersall, 2005;Levitan & Nardi, 2009). The aim of the present research is to examine the relative importance of state anxiety and trait anxiety in affecting children's social skills and the accuracy of self-perceptions.…”
Section: State Anxiety and Social Skillmentioning
confidence: 99%
See 2 more Smart Citations